Application of incomplete self-similarity argument for predicting bed-material load discharge - Cheng, Nian-Sheng (2012)
By applying the incomplete self-similarity argument, this study presents a structural analysis of models for predicting bed-material load discharge, which can be formulated consistently according to the number of independent variables considered. The coefficients involved in the proposed models are calibrated with published laboratory and field data (comprising almost 6,600 records). In comparison with the six bed-material formulas that are recommended in the recently updated ASCE manual on sedimentation engineering, the proposed models show significant improvements on the prediction of bed-material load discharge. This study also implies that the model developed, based on regular regression analysis, can be enhanced by considering interaction terms of independent variables.